Synthesis of octyl mannoside: article / Nor Hanani Roslan - Roslan, Nor Hanani (2018)
The application of octyl mannose is widely used in industry like drug, pharmaceuticals, biochemistry etc. Since the complexity of natural mannoside, a simple structure that consists of a single alkyl chain with mannose head group is produce as alternative. As the synthetic octyl mannoside is a new molecular science, the content, purity and molecular structure are needed. The aims are to synthesis octyl mannoside and to analyze the thermal properties of octyl mannoside. The purity, content and molecular structure was identified using Nuclear Magnetic Resonance (NMR) while thermal characteristic was identified by Differential Scanning Calorimetry (DSC). It shows that the purity of octyl mannoside is 49%. Since the yield of the product is small and does not enough for DSC analysis, the thermal properties of octyl mannoside cannot be determined.